Penile neurovascular structure revisited: immunohistochemical studies with three‐dimensional reconstruction. (14th August 2017) - Yin, G. N.; Park, S.‐H.; Choi, M.‐J.; Limanjaya, A.; Ghatak, K.; Minh, N. N.; Ock, J.; Song, K.‐M.; Ryu, J.‐K.; Suh, J.‐K.
Summary: Penile erection is a neurovascular phenomenon that requires well coordinated and functional interaction between penile vascular and nervous systems. In order to provide a useful tool to examine pathologic changes in the erectile tissue, mainly focusing on penile neurovascular dysfunction, we established the technique to determine the differential distribution of endothelial cells, smooth muscle cells, pericytes, and nerve fibers in the mouse penis using immunohistochemical staining with three‐dimensional reconstruction. Immunofluorescent staining of penile tissue was performed with antibodies against CD31 (an endothelial cell marker), smooth muscle α ‐actin (SMA, a smooth muscle cell marker), NG2 (a pericyte marker), or βIII‐tubulin (a neuronal marker). We reconstructed three‐dimensional images of penile vascular or neurovascular system from stacks of two‐dimensional images, which allows volume rendering and provides reliable anatomic information. CD31‐positive endothelial cells, SMA‐positive smooth muscle cells, and NG2‐positive pericytes were evenly distributed and composed sinusoidal or venous wall. However, the endothelial layer of the cavernous artery or dorsal artery was mainly covered with smooth muscle cells and rarely associated with pericytes. The reconstructed three‐dimensional images clearly visualized typical wavy appearance of nerve fibers that evenly innervate to cavernous sinusoids, cavernous artery, dorsal vein, and dorsal artery. We observed a significant decrease in CD31‐positive endothelial cells, NG2‐positive pericytes, and βIII‐tubulin‐positive nerve fibers in the penis of diabetic mice compared with those in normal condition. Our protocol for immunofluorescent staining with three‐dimensional reconstruction will allow a better understanding of the penile neurovascular anatomy and may constitute a standard technique to determine the efficacy of candidate therapeutics targeting therapeutic angiogenesis or neural regeneration.